Acetylsalicylic Acid (ASA) on Hydroxyethylcellulose/Polyacrylamide Gel (HEC/PAAm) as a Proposal for a Dermatological Compress: Mathematical Modeling of ASA Release Kinetics - Claudia Alicia Castillo-Miranda; Carlos Fernando Castro-Guerrero; Hugo Alberto Velasco-Ocejo; Jorge Alberto Gonzalez-Sanchez; Gabriel Osmar Flores-Cerda; Claudia Esmeralda Ramos-Galvan; Jose Luis Rivera-Armenta; Ana Beatriz Morales-Cepeda (International Journal of Polymer Science)
Currently, acne in adolescents and adults is caused by an infection in follicles caused by hormonal changes, stress, water pollution, air, and earth; the last one comes into contact with the skin through the hands of patients. This project presents the incorporation of acetylsalicylic acid (ASA) to the hydroxyethylcellulose/polyacrylamide gel (HEC/PAAm) in the synthesis of gel or by its swelling. The results show us that the incorporation of ASA is possible by both methods; first, the incorporation by synthesis of degradation of the gel is more visible. The infrared spectroscopic analysis shows the functional groups of gel and ASA, 2921 and 2863 cm−1, whose assignments correspond to CH3 and CH2 groups, which are part of both the polymer and the ASA molecule, which confirms the interaction between the two groups. The microscopy photographs (SEM) show on the surface the drug in irregular whitish orthorhombic forms due to swelling; arborescent structures are observed in the case of the incorporation of the ASA drug by synthesis. Swelling kinetics has a Fickian form. The Higuchi model conforms to the release of ASA because the level of confidence is 90%. This gel was allowed to release 0.35 mg/hour, thus allowing the patient to have a continuous form of the release, in the affected area in a short period of time.